2018
DOI: 10.1007/s00521-018-3532-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Study on the spatial–temporal change characteristics and influence factors of fog and haze pollution based on GAM

Abstract: PM 2.5 (particulate matter) is an important object for air quality monitoring, and the research on related influence factors and diffusion process of PM 2.5 plays a key role in the fight against pollution of fog and haze. Based on the air quality monitoring data and related meteorological data of 16 districts of Beijing during November 2016 and December 2017, such methods as time-series analysis and nonparametric test are adopted to describe the variation trend of PM 2.5 concentration in space and time and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Thi et al, 2019;). Most of air quality studies reported that short-term exposure to particulate matter, PM 2.5 can be related to acute lower respiratory infection (Bates et al, 2018;Martins and Carrilho, 2020;Tan et al, 2019;Wu, 2019). However, not only PM 2.5 , but PM 10 was also found to be have a significant relation with hospitalization due to the respiratory illness and pneumonia (Cheng et al, 2020;Chew et al, 2020;Ge et al, 2018;Luong et al, 2016;Mäkelä et al, 2019;Nephew et al, 2020;Pun et al, 2017;Rooij et al, 2019;.…”
mentioning
confidence: 99%
“…Thi et al, 2019;). Most of air quality studies reported that short-term exposure to particulate matter, PM 2.5 can be related to acute lower respiratory infection (Bates et al, 2018;Martins and Carrilho, 2020;Tan et al, 2019;Wu, 2019). However, not only PM 2.5 , but PM 10 was also found to be have a significant relation with hospitalization due to the respiratory illness and pneumonia (Cheng et al, 2020;Chew et al, 2020;Ge et al, 2018;Luong et al, 2016;Mäkelä et al, 2019;Nephew et al, 2020;Pun et al, 2017;Rooij et al, 2019;.…”
mentioning
confidence: 99%
“…The results showed that a low correlation between specific radioactivity concentrations of uranium isotopes and temperature in PM 2.5 (-0.18 to 0.48) and higher correlations in PM 2.5 of 40 K, 210 Pb and 232 Th with temperature (0.28-0.36). Temperature has been reported to be an atmospheric factor affecting reduction of the specific radioactivity isotopic concentrations (Wu and Zhang 2019). However, normally PM and related species increase in the winter with lower temperatures, lower mixed layer heights, and lower wind speeds.…”
Section: Correlations Among Activity Concentrations Of Isotopes With mentioning
confidence: 99%
“…In addition to meteorological factors [ 9 , 10 ], China’s economic development mode [ 11 , 12 ], industrial structure [ 13 , 14 ], and energy-use efficiency [ 15 , 16 ] lead to the frequent occurrence of hazy weather. Jin et al [ 17 ] pointed out that fine particulate matter (PM 2.5 ) in various provinces in China increased to different degrees from 2005 to 2014.…”
Section: Introductionmentioning
confidence: 99%